Worlding Asian American Literature: Transnationalism, Hemispherism, Planetarity. - Micheli, Grazia (2021)
This thesis explores the theme of mobility and the related concept of transnationalism through an analysis of selected works of contemporary Asian American literature by Meena Alexander, Jhumpa Lahiri, Hualing Nieh, Ruth Ozeki, Monique Truong and Karen Tei Yamashita. My study of the life and works of these authors shows how Asian Americans’ transnational links include the United States and their originary or ancestral country in Asia but also other countries located all around the world: in North and South America as well as in Europe. Thus, this dissertation contributes to a revision of transnational Asian American studies through an expansion of its East-West, U.S.-centred transpacific perspective towards a planetary model. Indeed, the cross-border links described and established by these writers exceed traditional definitions of transnationalism, which therefore prove to be inadequate to represent such a wide range of ties. Hence, I point to the ways in which these authors’ and their characters’ transnational ties can be described by other paradigms, able to highlight multilateral connections that happen at a national but also hemispheric and planetary level. This thesis also contributes to recent discussions of mobility that, while acknowledging the centrality of mobility in today’s world, do not uncritically praise it, considering instead how mobility is experienced differently according to factors such as ethnicity, class, gender and age. In order to critique celebratory or neutral understandings of mobility and transnationalism, I have coined the terms ‘negative mobility’ and ‘negative transnationalism’. Finally, my analysis goes beyond ethnographic or historiographic approaches to the study of Asian American literature as it highlights the formal aspects of the literary texts under examination, demonstrating how form has a central function to the narration. I especially focus on the role of languages other than English and of translingualism in these narratives since these linguistic features further emphasise the positioning of Asian American literature in the world.